Atmospheric Moisture Measurements Explain Increases in Tropical Rainfall Extremes. Issue 3 (2nd February 2019) - Roderick, Thomas P.; Wasko, Conrad; Sharma, Ashish
Abstract: Anthropogenic climate change is increasing extreme rainfall as a result of an increased water‐holding capacity of the atmosphere due to higher temperatures. However, observed rainfall‐temperature scaling relationships often differ from the theorized increases in moisture‐holding capacity. This discrepancy is most evident in the tropics, where higher surface temperatures show a marked decrease in extreme rainfall intensity despite observed increases in extreme rainfall. Here we use atmospheric moisture measurements from the National Aeronautics and Space Administration's Atmospheric Infrared Sounder with surface data to investigate the tropical rainfall‐temperature scaling relationship. We show rainfall intensity scales positively with integrated water vapor in all regions. Further, integrated water vapor does not consistently scale positively with surface air temperature and its dependence on background temperature offers a physical explanation for the apparent negative scaling. We conclude that the inconsistent relationship between surface air temperature and moisture is the reason for the "apparent" negative scaling consistently found in the tropics. Plain Language Summary: Rainfall scaling studies have been used to understand how we can expect extreme rainfall intensities to change under a warming global climate. Previous studies have consistently found negative scaling in the tropics, which contradicts the expectations that higher temperatures will result in more extreme rainfall and greater flood risk. This study shows that the negative scaling rates calculated in previous research may be caused by a limitation of temperature especially in climates with a surplus of moisture. It is reasoned that when moisture is available, excess heat results in more evaporation as opposed to an increased air temperature, forcing temperature to remain below a nominal upper limit. The study was performed using satellite measurements of integrated water vapor to give an accurate relationship between extreme rainfall and atmospheric moisture, as well as between surface air temperature and atmospheric moisture. Key Points: Negative scaling in the tropics can be explained by the limitation of temperature due to evaporation Extreme rainfall is found to scale consistently with integrated water vapor regardless of location Global warming can be expected to bring higher extreme rainfall events in all locations, including the tropics